The effect of additional flour of bean sprouts on organoleptic quality and nutritional content of semprong cake - Widia Dara; Nur Rahmadita (Alma Ata University Press, 2021)
ABSTRAK Latar belakang: Nilai zat gizi makro yang terdapat pada kecambah kacang hijau pada usia kecambah 24 jam yaitu protein 30,47%, lemak 0,44%, karbohidrat 65,97%. Kecambah atau toge zat gizinya lebih mudah diserap tubuh.Tujuan: Untuk menganalisis mutu organoleptik kue semprong yang ditambahkan tepung kecambah kacang hijau dan kandungan gizinya.Metode: Penelitian ini bersifat eksperimen dengan menggunakan Rancangan Acak Lengkap (RAL) dengan perlakuan A (100% tepung beras), B (100 % tepung beras dan 10 % tepung kecambah), C (100 % tepung beras dan 20 % tepung kecambah), D (100 % tepung beras dan 30 % tepung kecambah). Dilakukan pengulangan sebanyak dua kali. Untuk mengetahui pengaruh perlakuan dilakukan uji organoleptik pada warna, aroma, tekstur dan rasa kue. Analisis yang dilakukan sidik ragam (ANOVA)dan bila F hitung besar dari F tabel dilanjutkan dengan uji Duncan New Multiple Test (DNMRT). Analisis kandungan gizi dilakukan di laboratorium balai riset dan standardisasi industri kota Padang. Parameter yang di analisis adalah sifat sensoris, kadar air, abu, lemak, protein dan karbohidrat, kalium dan kalsium. Hasil: Terdapat pengaruh penambahan tepung kecambah terhadap aroma, tekstur dan rasa kue semprong. Tidak ada pengaruh penambahan tepung kecambah terhadap warna kue semprong. Kue semprong perlakuan C (100% tepung beras dan 20% tepung kecambah) yang paling disukai panelis dan merupakan formula yang tepat. Kandungan gizi kue semprong C yang meliputi kadar air, abu, lemak dan protein berturut turut adalah 4,30%, 1,17%, 21,18%, dan 7,30%, dan kadar karbohidrat 53,36%. Bila dibandingkan dengan kue semprong kontrol terjadi peningkatan kandungan protein, karbohidrat dan kadar air kue semprong. Sedangkan kandungan gizi lainnya menurun. Kesimpulan: Hasil penelitian ini didapatkan kue semprong yang dipilih dan disukai adalah yang ditambahkan 20 % tepung kecambah kacang hijau dari tepung beras. Kue semprong meningkat kandungan protein, karbohidrat dan kadar air.KATA KUNCI: kue semprong; tepung kecambah kacang hijau; tepung beras; organoleptik ABSTRACT Background: The value of macronutrients contained in bean sprouts at the age of 24 hours, namely protein 30.47%, fat 0.44%, carbohydrates 65.97%. Sprouts have nutrients that are more easily absorbed by the body.Objectives: The purpose of the study was to analyze the organoleptic quality of the semprong cake added with mung bean sprout flour and its nutritional content.Methods: This study is an experimental study using a completely randomized design (CRD) with A (100% rice flour, control), B (100% rice flour and 10% sprout flour), C (100% rice flour and 20% sprout flour), D (100% rice flour and 30% sprout flour). It was repeated twice. Parameters analyzed were organoleptic properties of semprong cake. The organoleptic test was by Analysis of variance (ANOVA) if significant, it was continued with the Duncan New Multiple Test (DNMRT). Analysis of the nutritional content was carried out in the laboratory of the research and industrial standardization center in the city of Padang. Nutritional analyses were water content, ash, fat, protein, carbohydrates, potassium, and calcium.Results: There is an effect of adding sprouted flour to the aroma, texture, and taste of the semprong cake. But no effect off adding sprouted flour on color semprong cake. The result of this research is that the selected and preferred semprong cake is that which is added 20% of mung bean sprout flour from rice flour. When compared with the control semprong cake, there was an increase in protein, carbohydrate, and water content. While the other nutritional content decreased. The nutritional content of the semprong cake is 4.30% water content, 1.17% ash content, 21.18% fat content, 7.30% protein content, and 53.36% carbohydrate content.Conclusions: The semprong cake treatment C (100% rice flour and 20% sprouted flour) was the most preferred by the panelists and was the right formula and increase in protein, carbohydrate, and water content. KEYWORDS: mung bean sprout fluor; organoleptic; rice flour; semprong cake